Impact of improving severity of secondary mitral regurgitation on survival. (25th October 2022) - Sannino, Anna; Banwait, Jasjit K.; Sudhakaran, Sivakumar; Rahimighazikalayeh, Gelareh; Szerlip, Molly; Smith, Robert; Esposito, Giovanni; Mack, Michael J.; Grayburn, Paul A.
Abstract: Aims: Secondary mitral regurgitation (SMR) is frequent in patients with heart failure with reduced ejection fraction (HFrEF) and portends detrimental prognosis. Despite interventions addressing the mitral valve (MV) have been proven effective to improve survival, an important knowledge gap exists regarding the role of medical therapy (MT) in this context. Thus, we aimed at investigating the role of MT optimization in patients with SMR and HFrEF. Methods and results: A total of 435 patients with SMR and HFrEF were retrospectively evaluated. Of those, 158 with severe SMR were finally included, with 63 (40%) managed with MT alone and 96 (60%) with MV intervention plus MT. Echocardiography was performed after 30 days of MT optimization or MV intervention. Responders were patients with a final mitral regurgitation (MR) grade of ≤2+. Survival data were gathered through the National Database Index and patient chart review. MR severity improved in 131 patients (100% MV intervention; 57% MT) but stayed the same or worsened in 27 patients. Responders and non‐responders were similar for baseline characteristics. Overall, long‐term survival of responders was significantly higher than non‐responders [hazard ratio (HR) 0.55, 95% confidence interval (CI) (0.32–0.96), P = 0.032]. No difference in survival was observed when evaluated by intervention type in the overall population (MT alone, n = 63; MV intervention plus MT, n = 95) [HR 0.77, 95% CI (0.48–1.26), P = 0.3], nor within responder group (MT alone, n = 36; MV intervention plus MT, n = 95) [HR 1.03, 95% CI (0.56–1.89), P = 0.94]. Conclusions: MT reduces SMR severity in 57% of the patients with severe SMR. A final SMR grade of ≤2+ is linked to improved survival, independently of the type of treatment they receive.